STUDY OF THE KINEMATIC AND DYNAMIC OF INTERACTION OF A VIBRATING SYSTEM FOR CUTTING OPTICAL SLUGS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the article, studies of the kinematics and dynamics of interaction of the elements of the vibration system "slug-cut disk" are made. A mathematical model describing the trajectory of a cutting arm has been created and the technological parameters of the system at which the phenomenon of resonance occurs have been determined.